Mortality Among Hardmetal Production Workers: Swedish Measurement Data and Exposure Assessment. Issue 12 (December 2017) - Westberg, Håkan; Bryngelsson, Ing-Liss; Marsh, Gary; Kennedy, Kathleen; Buchanich, Jeanine; Zimmerman, Sarah; Esmen, Nurtan; Svartengren, Magnus
Abstract : Background: Mortality pattern was determined in a cohort of 16, 999 white and blue-collar workers in the Swedish hardmetal industry. Exposure assessment for cobalt is presented. Methods: A historical database (1970 to 2012) of personal and area measurements of cobalt, tungsten, and nickel in the Swedish hardmetal industry was created. Log linear and exponential modeling of cobalt concentrations based on time period, job, and site was performed, and cumulative and mean exposures were calculated. Results: Some 37% of the personal cobalt measurements exceeded 0.02 mg/m 3, mostly for powder production, pressing, and shaping. The log linear regression showed statistical differences ( P  < 0.05) between sites, time periods, and jobs. Some 1.6% of the cobalt cumulative exposures for blue-collar workers exceeded 0.4 mg/m 3 years. Conclusion: Low levels of cumulative and mean exposures were determined.